Analysis of a simulated sprint competition in classical cross country skiing - Stöggl, T.; Lindinger, S.; Müller, E. (Scandinavian Journal of Medicine & Science in Sports, 2007)
The objectives of this project were first to analyze the physiological response of a classical cross country (XC) skiing sprint competition, second, to examine the relationships of kinematic and physiological variables with sprint performance and third, to test the hypothesis that maximal speed in double poling (DP) and diagonal stride (DIAG) predicts sprint performance. Twelve elite skiers performed a treadmill-based simulation of a sprint competition that included two maximal speed tests (DP, DIAG), a test and three sprint heats over a 3.5-h period. VO2, lactate, heart rate (HR) and kinematic variables were measured. Maximal DP and DIAG speed, the level of repeatedly produced lactate values and skiing technical aspects positively correlated with sprint performance. Fastest skiers produced longer cycle lengths in all techniques at equal poling frequency. VO2 variables showed no correlation to sprint performance. VO2, tidal volume (VT), and lactate decreased over the heats. XC-sprint performance in classical style depends on speed abilities, technique use, fatigue resistance, and anaerobic capacity. The relationship of maximal speed with sprint performance suggests (a) integrating maximal speed tests in XC sprint diagnostics and (b) emphasizing training models for XC skiing-specific speed abilities to improve performance in XC skiing sprint.